Sistem Pendukung Keputusan Seleksi Peserta Pelatihan di UPTD BLKK Kolaka dengan Metode TOPSIS - Hidayatullah, Muh. Ilham; Sunyanti, Sunyanti; Syaban, Kharis (Journal Research on Computing Knowledge, 2025)
The participant selection process for training at UPTD BLKK Kolaka remains manual, resulting in inefficiency and potential subjectivity in decision-making. This paper formulates a Decision Support System (DSS) utilizing the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) technique to resolve this issue. This method is selected for its ability to yield optimal participant recommendations by evaluating proximity to both positive and negative ideal solutions. The system is constructed utilizing PHP and MySQL for the storage of participant data and computation outcomes. The research phases encompass needs analysis, system design, implementation, and testing using Black Box Testing. The outcomes of manual and system calculations demonstrate consistency in preference values, confirming that the TOPSIS method effectively identifies the most appropriate training participants. This approach accelerates the selection process, enhancing transparency and objectivity. The deployment of a TOPSIS-based Decision Support System is anticipated to enhance efficiency and precision in decision-making, guaranteeing that chosen participants fulfill the requisite requirements